ANALISIS PENGISIAN FORMULIR RESUME MEDIS DIABETES MELLITUS PASIEN RAWAT INAP - Ratri Wulandari; Sri Sugiarsi (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
AbstractResume is a medical form that must be preserved. This sheet must be signed by the treating physician. Basedon a preliminary survey in dr. Sayidiman Magetan, in Medical Resume form filling in patients with DiabetesMellitus as much as 60% of the medical records of 67 documents found incomplete filling out the form onthe patient’s state of the item and the name of the doctor. The purpose of this study is to analyze the chargingForm Resume Medical Inpatient Diabetes Mellitus period fourth quarter of 2013 in the General Hospital dr.Sayidiman Magetan. This research is a descriptive retrospective approach. The population in this study isthe overall medical resume form in patients with Diabetes Mellitus as many as 67 medical record documents.Sampling technique with saturated sampling techniques and sample documents used were 67 medical recordsof the total population. Research instrument was a checklist. Way of collecting data through observation andunstructured interviews. The results were obtained form filling medical resume (unfilled) diagnosis largestitem that is present in 100% (67 documents) and form filling medical resume (not filled), the largest state ofthe items out there on the 62.68% (42 documents). State of the item not being filled out due to circumstancesout of patients already written in summary form Round. The results of this study it can be concluded that theneed to increase the rigor and discipline to the officer in charge of filling administrative data, clinical dataand authentication, the need for cooperation between medical records personnel to other units, especiallydoctors and nurses in the medical record to complete the form.Keywords: Analysis, Charging Resume MedicalAbstrakResume medis merupakan formulir yang harus diabadikan. Lembar ini harus ditandatangani oleh dokteryang merawat. Berdasarkan survei pendahuluan di RSUD dr. Sayidiman Magetan, dalam pengisian formulirResume Medis pada pasien Diabetes Mellitus sebanyak 60% dari 67 dokumen rekam medis ditemukanketidaklengkapan pengisian formulir pada item keadaan keluar pasien dan nama dokter. Tujuan penelitian iniadalah menganalisis pengisian Formulir Resume Medis Diabetes Mellitus Pasien Rawat Inap periode TriwulanIV tahun 2013 di Rumah Sakit Umum Daerah dr. Sayidiman Magetan. Jenis penelitian ini adalah deskriptifdengan pendekatan retrospektif. Populasi dalam penelitian ini adalah keseluruhan formulir Resume Medis padapasien Diabetes Mellitus yaitu sebanyak 67 dokumen rekam medis. Teknik pengambilan sampel dengan tekniksampling jenuh dan sampel yang digunakan adalah 67 dokumen rekam medis dari total populasi yang ada.Instrument penelitian adalah checklist. Cara pengumpulan data yaitu dengan observasi dan wawancara tidakterstruktur. Hasil penelitian diperoleh pengisian formulir Resume Medis (terisi) terbesar terdapat pada itemdiagnosis yaitu 100% (67 dokumen) dan pengisian formulir Resume Medis (tidak terisi) terbesar terdapat padaitem keadaan keluar yaitu 62,68% (42 dokumen). Tidak terisinya item keadaan keluar dikarenakan keadaankeluar pasien sudah tertulis pada formulir Ringkasan Pulang. Hasil penelitian ini dapat disimpulkan bahwaperlu adanya peningkatan ketelitian dan kedisiplinan kepada petugas yang bertanggungjawab dalam pengisiandata administratif, data klinis maupun otentikasi, perlu adanya kerjasama antara petugas rekam medis denganunit lain khususnya dokter dan perawat dalam melengkapi formulir rekam medis.Kata Kunci: Analisis, Pengisian Resume Medis, Rawat Inap